CD66 identifies a neutrophil-specific epitope within the hematopoietic system that is expressed by members of the carcinoembryonic antigen family of adhesion molecules. - Watt, S; Sala-Newby, G; Hoang, T; Gilmore, D; Grunert, F; Nagel, G; Murdoch, S; Tchilian, E; Lennox, E; Waldmann, H (1991)
Preliminary results from the IVth Leucocyte Culture Conference have classified the monoclonal antibody (MoAb), YTH 71.3.2, as CD66. Two other MoAbs, YPC 2/12.1 and CE6/2D3.1, share a common cellular specificity, reacting with cells of the neutrophil series and colonic epithelium. The YTH 71.3.2 and CE6/2D3.1 MoAbs both recognize a similar CD66 defined epitope that is distinct from that identified by YPC 2/12.1. By Western blotting, these antibodies react with different molecular species from cells of different lineages. The antibodies identify 50- to 55-Kd, 80- to 100-Kd, and 130- to 200-Kd components present in a semi-purified carcinoembryonic antigen (CEA) preparation from colonic adenocarcinomas and a 90- to 130-Kd molecule from HL-60 cells. With the colonic cell line, LS174T, YPC2/12.1 stains diffuse bands of 160 to 200 Kd and 90 to 130 Kd with equal intensity, whereas the binding of CE6/2D3.1 and YTH 71.3.2 is biased toward the lower molecular weight set of molecules. Remarkably, all three antibodies recognize CEA-related molecules. Defined analyses using HeLa cells transfected with CEA, NCA(NCA-50/90), and CGM6(NCA-95) cDNAs show that the three MoAbs identify CEA to varying degrees. While YTH 71.3.2 and CE6/2D3.1 also bind to NCA-50/90, YPC 2/12.1 recognizes an epitope expressed by both the NCA-50/90 and NCA-95 molecular species.